Documentation of infanticide in American Marten (Martes americana) - Dubruiel, Amy; Woodford, James E.; MacFarland, David M. (The Canadian Field-Naturalist, 2013)
Reports of male American Martens (Martes americana) interacting with pre-weaned kits are limited. During the post-release monitoring of American Martens translocated from Minnesota to northwestern Wisconsin in 2008–2010, we documented a male American Marten without a radio-collar ascending a den tree of a radio-collared female in 2011 and removing two pre-weaned kits. The female’s movements immediately became unrestricted after the removal. We also documented two events where an uncollared male American Marten was at the den tree before and after the kit removal. Only female American Martens have been reported to provide care for kits. Visual inspection of the remote camera photographs suggests that all three events likely involved the same uncollared male American Marten. This is the first record of a male American Marten killing pre-weaned kits.